Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/srep17389
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented mitochondrial genomes in two suborders of parasitic lice of eutherian mammals (Anoplura and Rhynchophthirina, Insecta)

Abstract: Parasitic lice (order Phthiraptera) infest birds and mammals. The typical animal mitochondrial (mt) genome organization, which consists of a single chromosome with 37 genes, was found in chewing lice in the suborders Amblycera and Ischnocera. The sucking lice (suborder Anoplura) known, however, have fragmented mt genomes with 9–20 minichromosomes. We sequenced the mt genome of the elephant louse, Haematomyzus elephantis – the first species of chewing lice investigated from the suborder Rhynchophthirina. We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 40 publications
(80 reference statements)
5
59
0
Order By: Relevance
“…The metazoan mitochondrial genome (mitogenome) is typically a circular double strand DNA molecule, encoding 13 protein‐coding (PCG) genes (seven subunits of the NADH dehydrogenase complex, the cytochrome b subunit of the cytochrome bc1 complex, three subunits of the cytochrome c oxidase, and two subunits of ATP synthase), 22 transfer RNAs (tRNA) genes, two ribosomal RNAs (rRNA, rrnS , and rrnL ) genes, and a control region (CR) including sites for the initiation of transcription and replication (Boore, ). Owing to its small genome size, higher evolutionary rates, limited recombination, and maternal inheritance, (Gissi, Iannelli, & Pesole, ; Simon, Buckley, Frati, Stewart, & Beckenbach, ), mitogenome has been widely used in species identification (Fu, Han, & Xiao, ; Kanmiya et al, ), molecular evolution (Cameron, ; Shao et al, ; Shao, Zhu, Barker, & Herd, ), phylogenetic relationship (Cameron, ; Cameron, Yoshizawa, Mizukoshi, Whiting, & Johnson, ; Chen, Wei, Shao, Dou, & Wang, ; Chen, Wei, Shao, Shi, et al, ), and population genetic (Wei et al, ; Zhang et al, ) studies. Although the gene content is relatively conservative, their rearrangements have been frequently reported, particularly in invertebrates at many taxonomic levels (Cameron, Johnson, & Whiting, ; Hassanin, Léger, & Deutsch, ).…”
Section: Introductionmentioning
confidence: 99%
“…The metazoan mitochondrial genome (mitogenome) is typically a circular double strand DNA molecule, encoding 13 protein‐coding (PCG) genes (seven subunits of the NADH dehydrogenase complex, the cytochrome b subunit of the cytochrome bc1 complex, three subunits of the cytochrome c oxidase, and two subunits of ATP synthase), 22 transfer RNAs (tRNA) genes, two ribosomal RNAs (rRNA, rrnS , and rrnL ) genes, and a control region (CR) including sites for the initiation of transcription and replication (Boore, ). Owing to its small genome size, higher evolutionary rates, limited recombination, and maternal inheritance, (Gissi, Iannelli, & Pesole, ; Simon, Buckley, Frati, Stewart, & Beckenbach, ), mitogenome has been widely used in species identification (Fu, Han, & Xiao, ; Kanmiya et al, ), molecular evolution (Cameron, ; Shao et al, ; Shao, Zhu, Barker, & Herd, ), phylogenetic relationship (Cameron, ; Cameron, Yoshizawa, Mizukoshi, Whiting, & Johnson, ; Chen, Wei, Shao, Dou, & Wang, ; Chen, Wei, Shao, Shi, et al, ), and population genetic (Wei et al, ; Zhang et al, ) studies. Although the gene content is relatively conservative, their rearrangements have been frequently reported, particularly in invertebrates at many taxonomic levels (Cameron, Johnson, & Whiting, ; Hassanin, Léger, & Deutsch, ).…”
Section: Introductionmentioning
confidence: 99%
“…Highly fragmented mitochondrial genomes in lice were first identified in human lice (Pediculus humanus) (Shao et al 2009), and minicircle-type mitochondrial genomes have since been confirmed in several other genera of sucking lice (Anoplura; Jiang et al 2013, Dong et al 2014a,b, Herd et al 2015, Shao et al 2017, elephant and warthog lice (Rhyncophthirina; Shao et al 2015), and chewing lice in the family Trichodectidae (Cameron et al 2011, Song et al 2019). Phylogenetic analyses have indicated that these three lineages of mammalian lice form a monophyletic group, which suggests highly fragmented mitochondrial genomes evolved once in the common ancestor of this group, as suggested by Song et al (2019).…”
Section: Evolutionary Implications For Highly Fragmented Mitochondriamentioning
confidence: 98%
“…The most highly studied group of organisms with multipartite circles are the mammalian blood-sucking lice in the suborder Anoplura, which have from nine to 20 circles of relatively similar sizes ranging from ~2 to 5 kb [14–18]. Recently, a similar multipartite arrangement was found in the closely related chewing lice suborder Rhynchophthirina [9]. The first metazoan circular multipartite genome to be reported was in a potato cyst nematode (PCN), Globodera pallida , which was shown to have at least six mtDNA circles ranging in size from ~6 to 9 kb [19].…”
Section: Introductionmentioning
confidence: 99%